2016
DOI: 10.1002/glia.23040
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the functional expression of the Ca2+-activated K+channel KCa3.1 on microglia from adult human neocortical tissue

Abstract: The K 3.1 channel (KCNN4) is an important modulator of microglia responses in rodents, but no information exists on functional expression on microglia from human adults. We isolated and cultured microglia (max 1% astrocytes, no neurons or oligodendrocytes) from neocortex surgically removed from epilepsy patients and employed electrophysiological whole-cell measurements and selective pharmacological tools to elucidate functional expression of K 3.1. The channel expression was demonstrated as a significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…While human T cells already express roughly 250 K V 1.3 channels in the resting state, rat and mouse T cells typically only express a very small number of channels (∼5) in the resting state and then up‐regulate K V 1.3 expression after activation (Beeton and Chandy, 2005; Beeton et al, ; Decoursey et al, ). Interestingly, another group very recently patch‐clamped adult human microglia from neocortical tissue surgically removed from epilepsy patients and found high K Ca 3.1 current densities (∼580 per cell), which, similar to our observations here, did not significantly change with LPS or IL‐4 treatment (Blomster et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…While human T cells already express roughly 250 K V 1.3 channels in the resting state, rat and mouse T cells typically only express a very small number of channels (∼5) in the resting state and then up‐regulate K V 1.3 expression after activation (Beeton and Chandy, 2005; Beeton et al, ; Decoursey et al, ). Interestingly, another group very recently patch‐clamped adult human microglia from neocortical tissue surgically removed from epilepsy patients and found high K Ca 3.1 current densities (∼580 per cell), which, similar to our observations here, did not significantly change with LPS or IL‐4 treatment (Blomster et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…A recent article reported that neocortical microglia isolated and cultured from human epilepsy patients responded to LPS with an increase in TNF-α production but no change in KCa3.1 expression. In contrast, IL-4 slightly increased the KCa3.1 current per cell, although no significant change in channel density was observed (Blomster et al 2016). Thus, although previous studies using cultured neonatal microglia suggest a pro-inflammatory role of KCa3.1 (Kaushal et al 2007; Maezawa et al 2011; Schlichter et al 2010), its actual functional roles in adults appear complicated and need to be verified by in vivo experiments as exemplified by this study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, no KCa3.1 current was seen in juvenile mouse microglia within acute brain slices (Schilling and Eder, 2007 ); whereas in adult microglia isolated using CD11b-coated magnetic beads, there were KCa3.1 currents in some microglia at 8 days after ischemia, and in most microglia isolated from LPS-injected mouse brains (Chen et al, 2016 ). In adult human microglia from epilepsy patients, most cells expressed a KCa3.1 current, which was unaffected by LPS and slightly increased by IL-4 (Blomster et al, 2016 ). Thus, a clear picture of KCa3.1 expression in microglia has not emerged.…”
Section: Discussionmentioning
confidence: 99%